Melanocytic nevus count and dermoscopic features do not differ in psoriatic patients undergoing biological agent versus conventional drug therapy - Su, Ozlem; PIRMIT, Serpil; ONSUN, NAHIDE; Onsun, NAHİDE; SU KÜÇÜK, ÖZLEM; OZKAYA, Dilek B. (My University, 2017)
BACKGROUND: Psoriasis is a chronic immune-mediated disease and treatment of psoriasis includes conventional immunosuppressive agents and biological agents. There are a few data on the relationship between psoriasis and melanocytic lesions. Either benign or malignant proliferations may be seen with immunosuppressive treatment. Eruptive nevi and malignant melanoma (MM) have been reported also associated with biological agents There is raising link biological treatment and malignancies. The objective of this paper is to examine the effects of biological agents versus conventional drugs on melanocytic nevi count and dermoscopical features.